Culture and neuroscience: How Japanese and European Canadians process social context in close and acquaintance relationships. (4th July 2019) - Russell, Matthew Joseph; Masuda, Takahiko; Hioki, Koichi; Singhal, Anthony
ABSTRACT: Recent cultural psychology findings suggest that social orientation affects neural social attention. Whereas independent cultures process people as separate from social context, interdependent cultures process people as dependent on social context. This research expands upon these findings, investigating what role culture plays in people's neural processing of social context for two relationship contexts, close and acquaintance relationships. To investigate, we had European Canadian and Japanese participants rate the emotions of center faces in face lineups while collecting ERP data. Lineups were either congruent, with all faces showing similar emotions, or incongruent, with center face emotions differing from background faces. To investigate relationship types, we framed face lineups to be in close or acquaintance relationships. We found that for acquaintances, only Japanese processed incongruent social context as meaningful, as seen through N400 incongruity effects. Contrasting with these patterns, only European Canadians showed N400 incongruity effects for close relationships. These patterns were seen whether or not the two groups noticed the emotional conflict, as seen by N2 incongruity effects. Finally, we found that social orientation was differentially related to the neural incongruity effects for the two relationships. These findings further elucidate the nuances of how culture affects neural social attention.